Economic burden of comorbid chronic conditions among survivors of stroke in China: 10-year longitudinal study - Ji Zhang; Suhang Song; Yang Zhao; Gaoting Ma; Yinzi Jin; Zhi-Jie Zheng (BMC, 2021)
Abstract Background The coexistence of chronic diseases among people with stroke is common. However, little is known about the extent of incremental healthcare expenditures associated with having physically and psychologically chronic conditions among stroke survivors. Methods We used the nationally representative data from the China Health and Nutrition Survey, including 36,076 participants enrolled as our analytic cohort of ten years of follow-up visits (2006, 2009, 2011, 2015). Chronic conditions include hypertension, diabetes, obesity, and impaired cognitive function. Two-part models were used to estimate the effect of comorbid chronic conditions on total annual healthcare expenditure, out-of-pocket (OOP) healthcare expenditure, and incidence of catastrophic healthcare expenditure (CHE). Results Among survivors of stroke during 2006 to 2015, the prevalence rates of hypertension, diabetes, obesity and impaired cognitive function were 75.5, 9.8, 12.7 and 65.1%, significantly higher than those among adults without stroke history (27.9, 2.7, 10.0 and 41.2%). Having hypertension ($794.5, p = 0.004), diabetes ($3978.5, p < 0.001) were associated with the largest incremental total healthcare expenditures. Stroke survivors with diagnosed hypertension and diabetes had additional 5.7 (p < 0.001) and 10.4 (p < 0.001) percentage point of CHE rate, respectively. Total healthcare expenditures were $2413.0 (P < 0.001) and $5151.7 (P < 0.001) higher among patients with 2, and ≥ 3 chronic conditions, respectively, than those individuals with no chronic conditions. Conclusions Excess expenditures associated with chronic diseases were substantial among stroke survivors. These results highlight the needs for both prevention and better management of multimorbidity among stroke survivors, which in turn may lower the financial burden of treating these concurrent comorbidities.